A Whole-Institution Approach Towards Sustainability at NOVA University: A Tangled Web of Engagement Schemes - J. Seixas; J. L. Rodrigues (Journal of Sustainability Perspectives, 2023)
Abstract. NOVA University Lisbon ambition to become a sustainable university following a whole-institution approach raises several challenges, due to the diversity of culture and governance of its nine schools spread over eight campuses in four municipalities. Engaging NOVA community is critical to achieve systemic changes, but very hard to carry coherently and at the same pace across all schools and throughout all its members. Different engagement schemes, interlinking a top-down one from the rector and the board of deans, who leads the vision, with several bottom-up schemes in education, research, value creation and operations are being implemented to carry out different purposes towards the common goal. NOVA for the Globe strategic platform and NOVA zero-waste task force are examples, among others, showing sustainability implementation at the university starts with people cooperation around the same ambition.Keyword: Strategic Thinking, Systemic Change, Engagement, University, Whole-Institution Approach.